The epidemiology of uterine fibroids: global disease burden from 1990 to 2021 and future trend predictions - Wu, Chan; Zhou, Ling; Chen, Ruilin; Li, Huiling; Li, Jian; Guo, Feifei; Li, Rong; Zhou, Huaijun; Huang, Jingjing (Frontiers in Reproductive Health, 2025)
BackgroundUterine fibroids (UF) are the most common benign tumors of the female reproductive system, imposing a significant health burden. A comprehensive understanding of their global, regional, and national burden is essential for targeted public health planning. This study aimed to analyze the spatiotemporal trends of UF burden from 1990 to 2021 and project future trends to 2036.MethodsData on the incidence, prevalence, and disability-adjusted life years (DALYs) of UF from 1990 to 2021 were extracted from the Global Burden of Disease (GBD) 2021 study, covering 204 countries and territories. We analyzed trends using estimated annual percentage changes (EAPC) for age-standardized rates. Socio-demographic Index (SDI) was used to assess the association between development level and disease burden. The Slope Index of Inequality (SII) and concentration index were employed to quantify health inequalities. A Bayesian age-period-cohort (BAPC) model was used to project the burden to 2036.ResultsBetween 1990 and 2021, the global ASIR of UF rose from 234.36 (95%UI: 171.06, 309.92) to 250.93 (183.44, 330.94) per 100,000 [EAPC 0.24 (0.23, 0.25)]. The ASPR increased from 2799.88 (2133.46, 3650.54) to 2841.07 (2164.43, 3682.27) [EAPC 0.04 (0.03, 0.06)]. DALYs grew from 81,142 (57,125, 111,989) to 142,885 (102,183, 192,988), while ASDR showed little change, from 3.48 (2.46, 4.77) to 3.39 (2.43, 4.59). Regional analysis indicated that South Asia exhibited the highest incidence and prevalence of UF, whereas Oceania and Australia experienced a lower burden. Analysis of health inequality revealed a shift in the burden of UF incidence and prevalence from high to low Socio-Demographic Index (SDI) countries between 1990 and 2021, indicating a reduction in health inequality. Future predictions from the BAPC model indicate that both ASIR and ASPR are expected to continue to rise, while ASDR is likely to decline.ConclusionsFrom 1990 to 2021, the global incidence of UF has steadily risen, with South Asia experiencing the greatest impact. Despite the stabilization of ASDR, the rise in ASIR and ASPR remains a significant public health challenge worldwide. Health inequality analysis indicates that the burden of UF is shifting toward low SDI countries. Future prevention and treatment strategies for UF should focus on middle- and low-income countries, specifically by implementing targeted screening programs, investing in low-cost diagnostic tools, and launching public health awareness campaigns. Global public health cooperation, along with early diagnosis and treatment strategies for UF, will be crucial in reducing the disease burden.